2019
DOI: 10.1111/ter.12418
|View full text |Cite
|
Sign up to set email alerts
|

Upper Pleistocene tectonics in western Sardinia (Italy): Insights from the Sinis peninsula structural high

Abstract: The Corsica-Sardinia block is a lithospheric fragment whose recent role in the geodynamics of the central-Western Mediterranean basin is still enigmatic. The most recent regional structure in Sardinia is the Plio-Pleistocene Campidano Basin, which is considered in a 'post-rift' stage since the Middle Pleistocene. New structural and stratigraphic geological surveys along with luminescence ages provide evidence to support an ongoing tectonic activity since the Marine Isotopic Stage 7 (MIS7; ca. 220 ka) on the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…While the analysis of this paper does not consider the Pliocene-Recent tectonic activity for the whole island, our fluvial inverse modelling results imply that landscape change caused by faulting can be resolved in areas of historically low tectonic activity such as Sardinia. For fault F2, we estimate that several metres of this landscape change occurred during the most recent glacial-interglacial cycles (MIS 5 to present), consistent with the interpretations of Mariani et al (2009), Polyak et al (2018) and Cocco et al (2019) who suggested tectonic activity in coastal regions over similar time periods.…”
Section: Implications For Pliocene-recent Tectonic Activity Of Sardiniasupporting
confidence: 88%
See 1 more Smart Citation
“…While the analysis of this paper does not consider the Pliocene-Recent tectonic activity for the whole island, our fluvial inverse modelling results imply that landscape change caused by faulting can be resolved in areas of historically low tectonic activity such as Sardinia. For fault F2, we estimate that several metres of this landscape change occurred during the most recent glacial-interglacial cycles (MIS 5 to present), consistent with the interpretations of Mariani et al (2009), Polyak et al (2018) and Cocco et al (2019) who suggested tectonic activity in coastal regions over similar time periods.…”
Section: Implications For Pliocene-recent Tectonic Activity Of Sardiniasupporting
confidence: 88%
“…Although Sardinia is generally considered to be currently tectonically inactive due to negligible historical seismicity (Angelone et al, 2005), deformation of last interglacial tidal notches and mapped faults within Late Pleistocene aeolian strata along the coast suggest that the Sardinia may have been tectonically 'active' during the late Quaternary (e.g. Mariani et al, 2009;Cocco et al, 2019). In addition, small normal faults are reported to offset the Basaltic Plains surface near the town of Macomer (e.g.…”
Section: Study Areamentioning
confidence: 99%
“…These latter populations are separated from others by Campidano graben, the greatest plain valley in Sardinia [63]. This plain was formed during the middle Pliocene and was submerged several times by marine transgression events [64,65] causing isolation. In addition, according to niche similarity tests, it seems that the Sardinian south-western populations occur in different climatic conditions with respect to all other populations from Corsica and Sardinia.…”
Section: Discussionmentioning
confidence: 99%
“…Sardinia is considered tectonically stable since the late Pliocene (Gueguen et al, 1998;Patacca et al, 1990), but minor vertical movements at metre scale in local areas have been recognized (Casini et al, 2020;Cocco et al, 2019).…”
Section: Geological Settingmentioning
confidence: 99%